Phosphorus and iron deficiencies influences rice shoot growth in an oxygen dependent manner: Insight from upland and lowland rice - Jenjira Mongon (2018)
© 2017 by the authors. Licensee MDPI, Basel, Switzerland. Rice is the main staple crop for one-third of the world population. To maximize yields, large quantities and constant input of fertilizers containing essential nutrients such as phosphorus (P) and iron (Fe) are added. Rice can germinate in both aerobic and anaerobic conditions, but the crosstalk between oxygen (O 2 ) and nutrients such as P and Fe on plant growth remains obscure. The aim of this work was to test whether such interactions exist, and, if so, if they are conserved between up- and lowland rice varieties. To do so, we assessed shoot and root biomass as well as inorganic phosphate (Pi) accumulation in four rice varieties, including two lowland rice varieties Nipponbare and Su phanburi 1 (SPR1) (adapted to non-aerated condition) and two upland rice varieties CMU122 and Sew Mae Jun (SMJ) (adapted to aerated condition) under various conditions of Pi and/or Fe deficiencies, in aerated and non-areated solution. Under these different experimental conditions, our results revealed that the altered shoot biomass in Nipponbare and SPR1 was O 2 -dependent but to a lesser extent in CMU122 and SMJ cultivars. In this perspective, discovering the biological significance and molecular basis of these mineral elements and O 2 signal interaction is needed to fully appreciate the performance of plants to multiple environmental changes.